The Sound Insulation of Double Facades with Openings for Natural Ventilation. Issue 3 (December 2015) - Bajraktari, Egzon; Lechleitner, Josef; Mahdavi, Ardeshir
Natural ventilation represents a potentially sustainable scheme for the provision of good indoor air quality and free cooling in buildings. Noise pollution is an impediment in this case, as buildings under noise exposure cannot effectively deploy the natural (window) ventilation option. The present contribution focuses on a double-leaf facade solution, which offers sufficient sound insulation while facilitating natural ventilation. The impact of various variables of such a system (e.g., the size of the opening, location of the openings, the relative displacement of the openings in the two layers, the cavity sound absorption) were examined via parametric laboratory sound transmission measurements using an experimental modular double-leaf wall. An empirically-based equation and a simple analytical one were developed for the prediction of the sound insulation of double-leaf facades with openings for natural ventilation. The results of these computational estimations are compared with the measurements results to discuss the potential and limitations of their predictive performance.